2024
DOI: 10.1186/s12934-023-02276-y
|View full text |Cite
|
Sign up to set email alerts
|

Bioproduction and optimization of newly characterized melanin pigment from Streptomyces djakartensis NSS-3 with its anticancer, antimicrobial, and radioprotective properties

Nessma A. El-Zawawy,
El-Refaie Kenawy,
Sara Ahmed
et al.

Abstract: Background Melanin is a natural pigment that is considered a promising biomaterial for numerous biotechnological applications across several industries. Melanin has biomedical applications as antimicrobial, anticancer, and antioxidant properties. Additionally, in the pharmaceutical and cosmetic industries, it is used in drug delivery and as a radioprotective agent. Also, melanin has environmental uses in the fields of bioremediation and the food industry. The biosynthesis of melanin pigment is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…The MelC1 protein determines the effective secretion of tyrosinase in the medium, but mutants, defective in the melC1 gene and thus in the secretion of the enzyme, have also been found [ 27 ]. In the literature, several new Streptomyces strains that can produce melanin were isolated from soil samples [ 22 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] from different locations in Egypt, India, and Turkey, or from forest or lake environments, also eventually associated with rhizosphere or plants [ 32 , 36 , 37 , 38 , 39 ] ( Figure 3 ). Some others, instead, have been isolated from marine sediments [ 40 , 41 , 42 , 43 , 44 , 45 ] in India and China, for example, or eventually associated with marine animals like the sea cucumber Stichopus vastus [ 46 ] ( Figure 3 ).…”
Section: Streptomyces Strains As Melanin Producersmentioning
confidence: 99%
See 2 more Smart Citations
“…The MelC1 protein determines the effective secretion of tyrosinase in the medium, but mutants, defective in the melC1 gene and thus in the secretion of the enzyme, have also been found [ 27 ]. In the literature, several new Streptomyces strains that can produce melanin were isolated from soil samples [ 22 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] from different locations in Egypt, India, and Turkey, or from forest or lake environments, also eventually associated with rhizosphere or plants [ 32 , 36 , 37 , 38 , 39 ] ( Figure 3 ). Some others, instead, have been isolated from marine sediments [ 40 , 41 , 42 , 43 , 44 , 45 ] in India and China, for example, or eventually associated with marine animals like the sea cucumber Stichopus vastus [ 46 ] ( Figure 3 ).…”
Section: Streptomyces Strains As Melanin Producersmentioning
confidence: 99%
“…The main reported carbon sources were glycerol, glucose, galactose, fructose, xylose, arabinose, rhamnose, raffinose, mannitol, inositol, sucrose, lactose, melibiose, starch, dextrose, and maltose [ 22 , 23 , 29 , 30 , 31 , 32 , 33 , 36 , 40 , 44 , 46 , 52 ], while both simple nitrogen sources, like ammonium sulfate, ferric ammonium citrate, sodium or potassium nitrate, ammonium chloride, ammonium nitrate, and urea, and complex nitrogen sources, like yeast extract, soybean meal, soy peptone, malt extract, beef extract, casein, casein peptone, meat peptone, and protease peptone, were exploited [ 22 , 23 , 29 , 31 , 32 , 34 , 40 ] ( Table 1 ). Many amino acids were included in different media like glycine, cystine, alanine, tryptophan, valine, leucine, proline, glutamine, aspartate, asparagine, phenyl alanine, and histidine, and L-tyrosine was often added to the medium as the first precursor of the biosynthetic pathway to enhance melanin production [ 31 , 34 , 35 , 40 , 44 , 52 ]. Salts like MgSO 4 , NaCl, FeSO 4 , K 2 HPO 4 , Na 2 HPO 4 , CaCO 3 , KCl, Na 2 S 2 O 3 , KH 2 PO 4 , CaCl 2 , NiCl 2 , FeCl 2 , MgCl 2 , ZnCl 2 , MnCl 2 , CaCl 2 , and CoCl 2 were tested as medium components, which affected the melanin production as well [ 29 , 31 , 44 ] ( Table 1 ).…”
Section: Biotechnological Strategies To Improve Melanin Production By...mentioning
confidence: 99%
See 1 more Smart Citation
“…Melanins are the oldest biological pigments synthesised by representatives of all kingdoms of life (Zhdanova & Vasilevskaya, 1988). They are known for their ability to absorb broad-spectrum radiation, serve as an antioxidant, a photoprotector that effectively absorbs and dissipates solar radiation in the form of heat, a sorbent that chelates metals and binds organic compounds, and an organic semiconductor (Barreto et al, 2023;El-Zawawy et al, 2024). Specifically, A.S. Abd-El-Aziz et al (2024), for melanin from the black fungus Curvularia soli AS21 ON076460, found antimicrobial, antiviral, and antitumour activity.…”
Section: Introductionmentioning
confidence: 99%